RESOLUTION OF DISPUTES REGARDING CORPORATE BONDS DECLARED BANKRUPT BY COMMERCIAL COURT - Rafie, Patih Ahmad; Merta, M. Martindo; Junaidi, Junaidi (Transpublika Publisher, 2024)
The objective of this study is to examine the resolution process for corporate bonds that have been declared bankrupt by the commercial court. This research adopts a normative legal approach, which involves analyzing the law as a comprehensive system comprising legal principles, norms, and rules. The findings of this analysis reveal that the Law of the Republic of Indonesia Number 8 of 1995, which pertains to the capital market, encompasses provisions on bonds. Additionally, article 1 number 3 of the finance ministerial regulation Number 27 of 2020 specifically regulates government securities (SUN) that qualify as bonds. These bonds have a maturity period exceeding one year and are accompanied by coupon payments and limited interest installments (discounts). Bonds can be interpreted as a form of liability protection offered by bond issuers to investors, along with an agreement to repay the principal amount and premium coupons at a predetermined time. Notably, in the case of a company or issuer being declared bankrupt, it is crucial to examine the settlement system for these bonds.